Po osobeno zhestok nachin . With Extreme Cruelty - Elezov, Rossen (B Plus, 2006)
Verzio FF Submission “With Extreme Cruelty” presents the sincere and moving confession of the well-known Bulgarian writer, playwright and editor Svoboda Buchvarova. The film features the mental and intellectual catharsis of Svoboda. The way she turned from an ardent communist into a passionate Christian is a key to understanding the drama of the last 60 years of Bulgarian history. She is trying to make peace with herself in a constant imaginary dialogue with the spirit of her father Theodor Angeloff, shot during the Second World War by the Gestapo and later declared a national hero of Belgium. It is the story of her trials and tribulations but also her personal metamorphoses.